Using Hypodermic Needle as Suture Needle in Emergency - Gupta, Sanjeev (J Cutan Aesthet Surg, 2020)
Sometimes, suture thread detaches from needle while suturing. This leads to wastage of left over thread and we have to repeat whole process of suturing as the extra suture needles are not easily available. The present article highlights the use of hypodermic needle as suture needle in such emergencies.